Lusófonas - Paiva, Carolina (Flora Filmes, 2019)
Women from Angola, Brazil, Mozambique and Portugal. Different colonized countries in three districts continents yet one single language. Lusophone Womens explores questions about what really remains from the colonist heritage; what they still keep and what have they overcome from the past. Their journeys, struggles and joy seems to be more familiar and closer than the geographic distance that separates them. --